Implementasi Aplikasi Elektronik Data Badan Usaha (E-Dabu) Dalam Pelayanan Kepesertaan Jamkesda di Kelurahan Duri Pulo Jakarta Pusat - syukron sazly; Himawan Pratama (Evolusi : Jurnal Sains dan Manajemen, 2020)
Abstract - Jaminan Kesehatan Daerah (Jamkesda) is a program of guarantee of health service assistance whose contributions are given by the Provincial Government to the underprivileged people who do not have any health insurance. In addition, Jamkesda is expected to overcome the problems of providing registration services to get free health insurance which is considered difficult to get the less fortunate citizens. In its implementation, Kelurahan Duri Pulo as one of the government agencies under the auspices of the Provincial Government of DKI Jakarta has been given the rules of registration service implementation. That is, in the form of Guidelines for Technical Socialization of National Health Insurance Registration- Healthy Indonesia Card for Jamkesda DKI. Meanwhile, this study aims to find out how the implementation of registration services Jamkesda DKI participants in Kelurahan Duri Pulo, Central Jakarta takes place. The Methods of data collection in this research used were observation, interview, and documentation technique . In this case, We observe the real daily implementation in this office, make interviews with a few staffs whose their duties were connected with this subject and obtain many documents that supported this research. The result of this research is  the implementation of registration service of Jamkesda DKI participants, based on membership registration requirement of Jamkesda DKI participants written on the list of participants who have registered  Jamkesda DKI participants has been running well, eventhough  some obstacles happened  that overcame perfectly. Keywords: Service, Registration, Implementation, Jamkesda DKI